Implementation of Outcome-Based Education (OBE) at Graduate School: Input for Competency Standard Development - CRESENCIO, MARION A.; PATIÑO, YEHLEEN CESCA M. (International Journal of Psychosocial Rehabilitation, 2020)
Universities and colleges envision excellence as a goal by providing their students with the highest quality education. To help fulfil this goal, schools began implementing outcome-based education (OBE) in 2012 with the directive of Commission on Higher Education (CHED). The purpose of this study is to determine the extent of OBE implementation at the Polytechnic University of the Philippines (PUP) Graduate School (GS). The researchers used the descriptive-correlative technique through a survey—utilizing OBE’s three (3) main areas: Learning Outcomes, Assessment Evidence, and Teaching and Learning Activities. Descriptive statistics such as mean, standard deviation, and ANOVA were used. The faculty of GS from PUP, Sta. Mesa, Manila, were regarded as participants for the second semester of academic year 2016-2017. Ninety two (92) out of one hundred five (105) faculty members responded to the study. Moreover, the extent of OBE’s implementation for all graduate program is broad in terms of degree—in regard with its three (3) areas—that each graduate program has diverse exposure and preparation. Therefore, graduate instructors should: (1) maximize their capacity in determining the student’s performance through a better curriculum—for a better education; (2) should organize an exchange of information to empower them to make adjustments and broadened the purview of OBE implementation.